INNOVATION TO IMPROVE THE EFFICIENCY OF AGRICULTURAL MACHINERY PRODUCTION SYSTEMS THROUGH COMMUNITY PARTICIPATION - Kheawyuong, Sorapong; Suksai, Samphan; P้hipatakesakul, Sompong; Thammalaksamee, Rujika; Gewnak, Naputr (Journal of Liberal Art of Rajamangala University of Technology Suvarnabhumi, 2024)
This research aimed to: 1. Analyze the issues and challenges faced by S. Rungruang Machinery Company Limited's agricultural machinery production system. 2. Analyze the techniques used to address the challenges in the agricultural machinery production system of S. Rungruang Machinery Company Limited. 3. Foster ideas to improve agricultural machinery manufacturing systems through community engagement. This research was qualitative. Through comprehensive interviews and group discussions, we assessed the execution of innovative strategies. A total of 37 individuals provided imperative information. The results of the research indicated that 1. Problems and obstacles of the agricultural machinery production system consist of four fundamental problems: 1) communication, 2) readiness of tools, machinery, and production system equipment, 3) production management, and 4) management. Guidelines for handling issues and obstacles in agricultural machinery production systems consisted of four approaches: 1) Guidelines for solving challenges in communication, 2) Guidelines for handling problems in the preparedness of tools, machinery, and equipment, 3) Guidelines for boosting process efficiency, and 4) Instructions for handling problems from management, and generating innovations to boost efficiency, developing agricultural machinery production system technology with participation from the community. It was found that there are three elements: 1) The process of developing production system technology, 2) The innovation and modernization of agricultural machinery, and 3) The ongoing development of people with creativity and unique ideas. The research findings can help develop an innovative model that aligns with the needs of stakeholders, resulting in value creation for the target group, business value generation, technical feasibility, and customer engagement.